Warm storage for arc magmas - Barboni, Mélanie; Boehnke, Patrick; Schmitt, Axel Karl; Harrison, T. Mark; Shane, Phil; Bouvier, Anne-Sophie; Baumgartner, Lukas (Proceedings of the National Academy of Sciences of the United States of America, 2016)
The increasingly popular notion that steady-state magma chambers are highly crystallized, and thus only capable of erupting during brief (<1 ka) reheatings, implies that melt detection beneath volcanoes warns of imminent eruption. By integrating the microgeochronology and geochemistry of zircons from lavas with those from components crystallized within the magma chamber and incorporated during eruption, we show that the Soufrière (Saint Lucia) volcanic reservoir was instead eruptible over long (>100 ka) timescales. Together with data from other volcanic complexes, we show that arc magmas may generally be stored warm (are able to erupt for >100 ka). Thus geophysical detection of melt beneath volcanoes represents the normal state of magma storage and holds little potential as an indicator of volcanic hazard., Felsic magmatic systems represent the vast majority of volcanic activity that poses a threat to human life. The tempo and magnitude of these eruptions depends on the physical conditions under which magmas are retained within the crust. Recently the case has been made that volcanic reservoirs are rarely molten and only capable of eruption for durations as brief as 1,000 years following magma recharge. If the “cold storage” model is generally applicable, then geophysical detection of melt beneath volcanoes is likely a sign of imminent eruption. However, some arc volcanic centers have been active for tens of thousands of years and show evidence for the continual presence of melt. To address this seeming paradox, zircon geochronology and geochemistry from both the frozen lava and the cogenetic enclaves they host from the Soufrière Volcanic Center (SVC), a long-lived volcanic complex in the Lesser Antilles arc, were integrated to track the preeruptive thermal and chemical history of the magma reservoir. Our results show that the SVC reservoir was likely eruptible for periods of several tens of thousands of years or more with punctuated eruptions during these periods. These conclusions are consistent with results from other arc volcanic reservoirs and suggest that arc magmas are generally stored warm. Thus, the presence of intracrustal melt alone is insufficient as an indicator of imminent eruption, but instead represents the normal state of magma storage underneath dormant volcanoes.
Gesehen am 19.08.2020